2011
DOI: 10.1038/modpathol.2011.73
|View full text |Cite
|
Sign up to set email alerts
|

All atypia diagnosed at stereotactic vacuum-assisted breast biopsy do not need surgical excision

Abstract: The necessity of excision is debatable when atypia are diagnosed at stereotactic vacuum-assisted breast biopsy (microbiopsy). Among the 287 surgical excisions performed at Institut Bergonié from 1999 to 2009, we selected a case-control study group of 151 excisions; 52 involving all the diagnosed cancers and 99 randomly selected among the 235 excisions without cancer, following atypical microbiopsy (24 flat epithelial atypia; 50 atypical ductal hyperplasia; 14 lobular neoplasia; 63 mixed lesions). Mammographica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 24 publications
4
12
1
3
Order By: Relevance
“…The histologic extent of ADH was also a significant predictor on multivariate analysis, 2.32 mm in cases with upgrade versus 1.77 mm in non‐upgrade cases. Similar to our findings, Mascarel et al found that upgrade was more likely as the histologic extent of the epithelial atypia increased. In the study by Khoury et al the histologic extent of ADH was also associated with upgrade, 1.42 mm for non‐upgrade cases and 2.09 mm for cases with upgrade.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The histologic extent of ADH was also a significant predictor on multivariate analysis, 2.32 mm in cases with upgrade versus 1.77 mm in non‐upgrade cases. Similar to our findings, Mascarel et al found that upgrade was more likely as the histologic extent of the epithelial atypia increased. In the study by Khoury et al the histologic extent of ADH was also associated with upgrade, 1.42 mm for non‐upgrade cases and 2.09 mm for cases with upgrade.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with the results from prior studies. Mascarel et al analyzed the rate of upgrade for lesions with epithelial atypia diagnosed on CNB and found that upgrade was significantly more likely as the number and percentage of cores with epithelial atypia increased. Khoury et al and Wagoner et al studied ADH diagnosed on CNB and showed that the rate of upgrade was significantly associated with the number of cores involved.…”
Section: Discussionmentioning
confidence: 99%
“…In our retrospective study, this would have translated to 32 (64%) actual excisions avoided (37 surgeries recommended minus the five surgeries deferred) (95% CI: 50%, 77%). more focally aggressive natural history, leading to frank malignancy in a substantial number of cases (33,(37)(38)(39). Obligatory surgical excision allows for increased volumetric analysis and removes review and none ultimately upgraded at surgery (malignancy rate, 0%; 95% CI: 0%, 8%).…”
Section: Discussionmentioning
confidence: 99%
“…The management of all B3 lesions has traditionally been open diagnostic surgical excision biopsy. However, it is increasingly recognised that some B3 subtypes are only associated with a very low risk of malignancy, and therefore, surgical excision for all represents overtreatment 3 4…”
Section: Introductionmentioning
confidence: 99%